The impact of leverage on financial performance of firms in Malaysia food industry / Oj Roger Sumail - Sumail, Oj Roger (2018)
Good financial firm performance is a goal to every firm, its shows that the firms have better management. In order to have better management of the firm it is important to know what is the best types of financing for the firm operations. This study aims to examine the relationship between financial leverage and financial performance of firms in Malaysia Halal food industry. The study used data from 10 Halal food industry firms listed in main board of Bursa Malaysia as at 31 December 2017. The timeframe for data collection is from 2010 to 2017. As the measurement for the financial performance whereby it is represent the dependent variable this study used return on assets (ROA) and as the measurement for the financial leverage this study used short term debt (STD), long term debt (LTD), and total debt (TD) which representing independent variable. The study was found that there is a significant positive relationship between LTD and ROA. On the other hand STD and LTD have significant negative relationship with ROA.